Nurses’ Personality Traits and Perceived Work Environments During Public Health Emergencies: Implications for Nursing Workforce Planning - Wang X; Shao J; Weng A; Lian J; Weng F; Fang Q; Hu Y (Dove Medical Press, 2024)
Xiyi Wang,1 Jing Shao,2 Aozhou Weng,1 Jiaqi Lian,1 Fule Weng,1 Qiong Fang,1 Yun Hu1 1School of Nursing, Shanghai Jiao Tong University, Shanghai, 200025, People's Republic of China; 2Institute of Nursing Research and Department of Nursing of Fourth Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310058, People's Republic of ChinaCorrespondence: Yun Hu, School of Nursing, Shanghai Jiao Tong University, Shanghai, 200025, People's Republic of China, Email huyunsy@shsmu.edu.cnBackground: The nursing workforce faces substantial challenges, particularly in the aftermath of the COVID-19 era. Developing an effective strategy for workforce maintenance and the strategic deployment of nurses is crucial.Purpose: This study aimed to explore and categorize nurses' personality traits, with a focus on analyzing differences in their perceptions of the nursing work environment.Participants and Methods: Between January 2023 and February 2023, a multi-center cross-sectional study was carried out involving nurses from 12 tertiary hospitals actively engaged in frontline COVID-19 response duties. Through cluster sampling, surveys were distributed among eligible nursing staff, comprising a general information questionnaire, the Chinese Big Five Personality Questionnaire-Short Form, subjective evaluations of emergency nursing management, and the Chinese Nursing Work Environment Scale for Public Health Emergencies. Various statistical analyses, such as descriptive analysis, cluster analysis, non-parametric tests, and general linear model analysis, were employed to investigate the correlation between personality types and the perception of nursing work environments.Results: The analysis encompassed 1059 valid questionnaires, reflecting the experiences of frontline nurses. The majority of these nurses possessed 1- 5 years of experience, held junior professional titles, volunteered for their roles, and served as attending nurses. Categorization based on personality traits revealed three groups: resilient (35.60%), ordinary (16.15%), and distressed (48.25%) types. Significantly distinct perceptions of nursing work environments emerged among these categories, with resilient and ordinary types expressing notably higher satisfaction compared to the distressed group (H value = 256.487, p < 0.001).Conclusion: This study illustrates the connection between nurses' perceived working environment and their personality traits. Nursing managers should factor in nurses' personality traits when choosing and deploying frontline responders during public health emergencies. Prioritizing resilient-type nurses and crafting a supportive work environment that aligns with nurses' characteristics is indispensable for an effective emergency response.Keywords: workforce management, cross-sectional studies, human resources, health system